Revision of the austral South American species of Mortoniella (Trichoptera: Glossosomatidae: Protoptilinae) - Blahnik, Roger J.; Holzenthal, Ralph W. (Zootaxa, 2011)
Species of Mortoniella are revised for the southern part of the South American continent, including the countries of Brazil, Paraguay, Uruguay, Argentina and Chile. The M. velasquezi species group is diagnosed for the first time and the M. bilineata species group is more critically defined. Males of all species from the region, except M. armata (Jacquemart, 1963), are figured, and a key is provided for their identification. Included in the revision are 11 described species and 22 new species. Previously described species that are redescribed and figured include the following: Mortoniella albolineata Ul-mer, 1907; M. argentinica Flint, 1974; M. catarinensis (Flint, 1974); M. collegarum (Rueda & Gibon, 2008); M. guairica (Flint, 1974); M. ormina (Mosely, 1939); M. pocita (Flint, 1983); M. punensis (Flint, 1983); M. teutona (Mosely, 1939); M. unota (Mosely, 1939); and M. wygodzinskii (Schmid, 1958). Mortoniella collegarum, originally described from Bolivia and Argentina, is here reported from Chile, representing the first distributional record of Mortoniella for that country. It is assigned to the M. ormina species group. On morphological considerations, M. argentinica is removed from the M. bilineata species group and left as a species incertae sedis as to species group. Based on its overall similarity to M. argentinica, M. spinulata (Flint, 1991), from Colombia, is removed from the M. leroda species group and left as a species incertae sedis as to species group. New species of Mortoniella described here, followed by their respective areas of distribution, include, for the M. leroda species group: Mortoniella acauda (SE Brazil), M. agosta (SE Brazil), M. asym- metris (Paraguay), M. crescentis (SE Brazil), M. dolonis (SE Brazil), M. guahybae (SE Brazil), M. hystricosa (SE Brazil), M. intervales (SE Brazil), M. latispina (SE Brazil), M. longispina (SE Brazil), M. paraguaiensis (Paraguay), M. parauna (SE Brazil), M. paraunota (Argentina, SE Brazil), M. pumila (SE Brazil), M. pusilla (SE Brazil), M. truncata (SE Brazil), and M. uruguaiensis (SE Brazil, Uruguay); for the M. ormina species group: M. alicula (SE Brazil); and for the M. velasquezi species group: M. bocaina (SE Brazil), M. froehlichi (SE Brazil), and M. tripuiensis (SE Brazil). A new species unplaced as to species group is M. meloi (SE Brazil).